1972
DOI: 10.2466/pr0.1972.31.2.391
|View full text |Cite
|
Sign up to set email alerts
|

Personality Characteristics of Women Scientists

Abstract: Women biologists and chemists listed in Who's Who in America and Who's Who of American Women ( N:146) were studied with the Sixteen Personality Factor Questionnaire (16 PF). As a group, women scientists were found to be more serious, radical, confident, dominant, intelligent, and adventurous than women in the general population, and less sociable, group-dependent, and sensitive. Personality profiles on the 16 PF of men and women scientists showed strong similarity ( p < .01).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…SCIENCE AND TECHNOLOGY Personality correlates of scientific achievement and creativity were studied in elementary school children (Milgram et al 1977); high school students (Schaefer & Anastasi 1968, Parloff et a1 1968, Anastasi & Schaefer 1969, Schaefer 1969a,b, Walberg 1969a; undergraduates, young adults, and graduate students (Rossman & Hom 1972, Schaefer 1973, Gough 1979, Korb & Frankiewicz 1979; psy chologists (Chambers 1964, Wispe 1965, Bachtold & Werner 1970; inven tors (Bergum 1975, Albaum 1976, Albaum & Baker 1977; mathematicians (Helson 1967b(Helson , 1968aParloff et al 1968;Helson & Crutchfield 1 970a,b;Helson 1971;Gough 1979); chemists (Chambers 1964); and assorted engi neers and research scientists (McDermid 1965, Owens 1969, Bachtold & Werner 1972, Bergum 1973, Eiduson 1974, Gough 1979.…”
Section: A Proliferation Of Studies In Many Fieldsmentioning
confidence: 99%
“…SCIENCE AND TECHNOLOGY Personality correlates of scientific achievement and creativity were studied in elementary school children (Milgram et al 1977); high school students (Schaefer & Anastasi 1968, Parloff et a1 1968, Anastasi & Schaefer 1969, Schaefer 1969a,b, Walberg 1969a; undergraduates, young adults, and graduate students (Rossman & Hom 1972, Schaefer 1973, Gough 1979, Korb & Frankiewicz 1979; psy chologists (Chambers 1964, Wispe 1965, Bachtold & Werner 1970; inven tors (Bergum 1975, Albaum 1976, Albaum & Baker 1977; mathematicians (Helson 1967b(Helson , 1968aParloff et al 1968;Helson & Crutchfield 1 970a,b;Helson 1971;Gough 1979); chemists (Chambers 1964); and assorted engi neers and research scientists (McDermid 1965, Owens 1969, Bachtold & Werner 1972, Bergum 1973, Eiduson 1974, Gough 1979.…”
Section: A Proliferation Of Studies In Many Fieldsmentioning
confidence: 99%
“…() developed norms for scientists – defined as biologists, chemists, geologists, and physicists – which indicated that, compared to the general population, they were less outgoing, enthusiastic, and conscientious; as well as more stable, assertive, and tender‐minded. Similarly, Bachtold and Werner () examined the personality traits of 146 female biologists and chemists and found that, compared to general population norms, they were more serious, radical, confident, dominant, intelligent, and adventurous, although less sociable, group‐dependent, and sensitive. In part, the earlier results are consistent with Roe's () observation that physical scientists are less social as well as more autonomous, absorbed in their work, and intrinsically motivated compared to nonscientists.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a few studies have been directed at creative women (Helson, 1966(Helson, , 1967(Helson, , 1971Bachtold & Werner, 1972, 1973Bruch & Morse, 1972). The bulk of this research, as is true of studies of gifted females in general (Blaubergs, 1978), has centered on the assessment of personality traits of creative females.…”
Section: Life Patterndcoping Strategiesmentioning
confidence: 99%